1994
DOI: 10.1155/mbd.1994.291a
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Organometallics. IV. The Mutagenic Potential of SomeDiphenylantimony(III) Dithiophosphorus Derivatives

Abstract: Two diphenylantimony(III) derivatives of dithiophosphorus ligands, i.e. Ph2SbS2PPh2 and Ph2SbS2P(OPr-i)2, which were previously found to exhibit antitumor properties, have been now investigated for potential mutagenic effects in healthy and Ehrlich ascites tumor-bearing mice. Two short-term tests, i.e. the micronucleus test and the cytogenetic analysis, were used as end-points for mutagenicity. The results are consistent with a mutagenic potential for both organoantimony(III) compounds tested, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 1 publication
0
14
0
Order By: Relevance
“…The antitumor screening and cytotoxicity of antimony(III) and antimony(V) compounds have also been reviewed by Tiekink [5]. The most studied antimony(III) compounds, in the context of antitumor activity, are organoantimony compounds, such as diphenylantimony(III) thiolates, i.e., [Ph 2 Sb(S 2 PPh 2 )] and [Ph 2 Sb(S 2 P(O i Pr) 2 )] [6][7][8]. Early studies of these compounds showed that either in vitro or in vivo they were more active than the corresponding organotin(IV) compounds against Ehrlich ascites tumor cell lines [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The antitumor screening and cytotoxicity of antimony(III) and antimony(V) compounds have also been reviewed by Tiekink [5]. The most studied antimony(III) compounds, in the context of antitumor activity, are organoantimony compounds, such as diphenylantimony(III) thiolates, i.e., [Ph 2 Sb(S 2 PPh 2 )] and [Ph 2 Sb(S 2 P(O i Pr) 2 )] [6][7][8]. Early studies of these compounds showed that either in vitro or in vivo they were more active than the corresponding organotin(IV) compounds against Ehrlich ascites tumor cell lines [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Diphenylantimony(III) dithiophosphorus complexes are active against Ehrlich ascites tumor cells in mice [81][82][83]; the most active compound is (diisopropylphosphorodithioato )diphenylantimony(III) [84]. Among the early transition metal compounds the metallocene complexes are of special interest.…”
Section: Antimony Bismuthmentioning
confidence: 99%
“…[ 32 ] Certain dialkyl dithiocarbamates are also used like scavengers in wastewater treatment and as floatation agents. [ 33–41 ] Dithiocarbamates used in the treatment of microbial infections as medicine and pyrrolidine iron dithiocarbamate accepted for the treatment of acquired immunodeficiency syndrome as these derivatives can block a transcription element involved in human immunodeficiency virus. [ 42 ] In addition, metal bonded antioxidants were noticed for their capacity to protect living creatures and cells from damage, produced by scavenging free radicals or oxidation stress.…”
Section: Introductionmentioning
confidence: 99%